PENDAMPINGAN PENYUSUNAN APLIKASI LAPORAN KEUANGAN MASJID YANG AKUNTABEL SESUAI PSAK 45 - Yulianti Yulianti; Ahmad Sahri Romadon; Risti Ulfi Hanifah (Publisher UPT P2M Politeknik Negeri Malang, 2020)
The purpose of this dedication is to design the Mosque Financial Report Application in accordance with the Financial Accounting Standards (PSAK-45) so that the financial report can be held accountable to the people who make a part of their wealth available to the mosque. This is one of the responsibilities given to the community giving infaq. But besides that the mosque management must also make financial reports that will later be reported to the mosque takmir and to all the managers, so that the financial statements can be arranged transparently so that there is no suspicion from any party and moreover as an accountability to Allah SWT. In preparing the accounting reports for non-profit entities, it has been regulated in the Financial Accounting Standards Guidelines (PSAK-45) that have been prepared by the Indonesian Institute of Accountants (IAI) as a compiler of accounting reports, so that the financial statements can be accountable to the public and can be read by parties parties with an interest in the financial statements. This activity was carried out in the form of outreach and assistance in making mosque financial reports with the systematic application of financial reports using the Microsoft Excel program. From the evaluation results that have been carried out that the results of this activity have been able to increase understanding and skills in preparing the mosque's financial statements in the form of Financial Position Reports, Activity Reports, Cash Flow Statements, and Equity Change reports.Keywords: entrepreurship , warehousing and ecoprint batik